2018
DOI: 10.1111/tmi.13158
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators for maternity waiting home utilisation at Attat Hospital: a mixed‐methods study based on 45 years of experience

Abstract: Objective To describe facilitators for maternity waiting home (MWH) utilisation from the perspectives of MWH users and health staff. Methods Data collection took place over several time frames between March 2014 and January 2018 at Attat Hospital in Ethiopia, using a mixed‐methods design. This included seven in‐depth interviews with staff and users, three focus group discussions with 28 users and attendants, a structured questionnaire among 244 users, a 2‐week observation period and review of annual facility r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 19 publications
4
39
1
Order By: Relevance
“…Decision making autonomy in a household was more likely to utilize the MWH as compared to a woman who had not the autonomy, this result is in line with the study done in Zambia(15), where women who had decision making autonomy used the MWH better when compared with those who had no decision making autonomy. In this study there is no association between MWH utilization and education level which is not similar with the study done at Attat Hospital southern Ethiopia(22), where educational level was associated with MWH utilization; The difference is might be the participants of this study were nearly in the same educational status ranges.…”
Section: Discussioncontrasting
confidence: 88%
“…Decision making autonomy in a household was more likely to utilize the MWH as compared to a woman who had not the autonomy, this result is in line with the study done in Zambia(15), where women who had decision making autonomy used the MWH better when compared with those who had no decision making autonomy. In this study there is no association between MWH utilization and education level which is not similar with the study done at Attat Hospital southern Ethiopia(22), where educational level was associated with MWH utilization; The difference is might be the participants of this study were nearly in the same educational status ranges.…”
Section: Discussioncontrasting
confidence: 88%
“…While our results show that an improved MWH model can result in measurably improved quality across multiple domains, there are likely additional drivers of utilization of MWHs at CEmONC facilities [22]. We observed a steep increase in the numbers of women utilizing any MWH for any reason at intervention sites and a slower increase over time at comparison sites (Fig 1, Table 7), which may be attributed to three key drivers.…”
Section: Discussionmentioning
confidence: 81%
“…This could be the reason why women in remote areas are not motivated to come to MWHs because the whole household is dependent on women for all household support [13]. On the contrary, studies in Attat hospital, Ethiopia [26], rural southern Egypt (Upper Egypt) [27], rural Zambia [28] and Sierra Leone [29] reported that husbands played important roles to encourage their wives to use MWHs. They possibly have positive attitudes towards MWHs and perceived benefits from using MWHs, including mitigating long distances and improving access to facility-based delivery care.…”
Section: Discussionmentioning
confidence: 99%